PENGARUH EKUITAS MEREK, KUALITAS PELAYANAN, DAN SWITCHING COST TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING Studi Kasus Pada PT Garuda Indonesia (Persero) Tbk Branch Office Semarang - Mahendra, Muhammad Habib; Waluyo, Handoyo Djoko; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
This research is motivated by the increasingly fierce competition as it is today. PT Garuda Indonesia, which is one of the airline companies in Indonesia today is also very aggressively to improve the quality of service that customer satisfaction is increased. For the initial step Garuda Indonesia to improve services to the customers ie rearranging operations and management of PT Garuda Indonesia flight to be on time and make Garuda Indonesia has the quality and service excellence. In particular, this study discusses the Garuda Indonesia service users who have not yet reached the target from year to year. From the data analysis it can be conclude that there is positive and significant correlation between the variables of brand equity, service quality, and the cost of switching to variable customer satisfaction partially and simultaneously, and there is a positive and significant effect among variables of customer satisfaction on customer loyalty variables.